Design and experimentation of two-coil coupling for electric city-car WPT charging. Issue 1 (2nd January 2016) - Mude, Kishore Naik; Bertoluzzo, Manuele; Buja, Giuseppe; Pinto, Rosanna
Abstract : The article deals with the two-coil coupling of an inductive wireless power transfer system intended to charge the battery of an electric city-car. At first, two-coil coupling structures with different arrangements for the coil windings and different shapes for the magnetic core are investigated. Investigation is carried out by help of a FEM code, and encompasses the determination of (i) the inductive parameters as a function of the coil distance and axial misalignment and (ii) the nearby electromagnetic fields to verify their admissibility for the humans. Afterwards the coil coupling is designed and then set up according to the results of the investigation. Measurements executed on the set-up validate the design for both the inductive parameters and the nearby electromagnetic fields.